Mid-Carpal Joint Sparing Procedure for Idiopathic Avascular Necrosis of Capitate - Ansari, Mohammed Tahir; Janardhanan, Ritvik (Journal of Wrist Surgery, 2020)
Background Avascular necrosis of the capitate (AVNC) is an uncommon pathology of the wrist. Several procedures have been described for the treatment of AVNC. The type of treatment varies depending upon the stages. In early stages, revascularization procedures are performed. If secondary osteoarthritis develops, then the treatment options include intercarpal fusion, four corner fusion, prosthesis replacement of the capitate, tendon interposition, and wrist arthrodesis. No long-term study is available for choosing an appropriate method of the treatment for AVNC.Case Description Herein, we report a case of AVNC that was managed by hemi-resection of the capitate with capito-hamate fusion and tendon interposition. One year after surgery, patient was asymptomatic and radiographs revealed fusion of capito-hamate joint and maintenance of the mid-carpal joint space. There was no evidence of carpal collapse.Literature Review All the literature about mid-carpal joint sparing (MCJS) procedures has been reviewed in this report. This is a goal behind writing of this case report as there have been very few publications about these procedures.Clinical Relevance This case illustrates the successful treatment of AVNC by MCJS procedure. The intercarpal fusion and the four corner fusion are one time procedures, and these can be used if the MCJS procedure fails or sometimes, as primary procedure, if the patient gives consent for the same. It appears prudent to save arthrodesis procedures for the future.
Keywords: avascular necrosis; capitates; mid-carpal joint; fusion